PENGARUH PAPARAN ASAP ROKOK TERHADAP KADAR MALONDIALDEHID DAN KELAINAN HISTOPATOLOGI GLANDULA LAKRIMAL TIKUS PERCOBAAN - Puji Indah Lestari (HUMAN CARE JOURNAL, 2022)
Introduction: Smoking is closely related to the increase in free radicals that cause damage to the lacrimal gland and inflammation of the corneal and conjunctival surfaces. Oxidative stress on the lacrimal gland causes inflammation of acinar cells. Immunohistochemical examination of the lacrimal glands of rats exposed to cigarette smoke showed an increase in CYP1A1 expression.Objective: To determine the effect of exposure to cigarette smoke on MDA levels and histopathology of the lacrimal gland in experimental ratsMethods: This study is an experimental study with a post-test-only design with a control group with the object of research being the Wistar white rat. This study consisted of two groups of samples with each group of 16 rats. Then MDA and histopathological examination of the lacrimal gland were performed. The research was conducted at the Laboratory of the Faculty of Pharmacy, Andalas University, the Anatomical Pathology Laboratory of Sitirahmah Hospital, Padang and the Biochemistry and Biomedical Laboratory of the Faculty of Medicine, Andalas University in July – September 2020.Results: From the results of the study, it appears that all rats exposed to cigarette smoke have histopathological abnormalities in the form of inflammatory cell infiltration accompanied by tissue damage and increased levels of MDA in the lacrimal gland. In the lacrimal glands of rats that were not exposed to cigarette smoke, there were normal histopathological features, but some were abnormal but without damage to tissue structures.Conclusion: The lacrimal glands of rats exposed to cigarette smoke have abnormal histopathological features accompanied by tissue structure damage and increased MDA levels. Keywords: lacrimal gland, cigarette smoke, MDA, histopathologyPendahuluan: Merokok berhubungan erat dengan meningkatnya radikal bebas yang menyebabkan kerusakan glandula lakrimal dan inflamasi permukaan kornea dan konjungtiva. Stres oksidatif pada glandula lakrimal menyebabkan inflamasi sel asinar. Pemeriksaan imunohistokimia glandula lakrimal tikus yang terpapar asap rokok menunjukkan peningkatan ekspresi CYP1A1.Tujuan: Mengetahui pengaruh paparan asap rokok terhadap kadar MDA dan histopatologi glandula lakrimal tikus percobaanMetode: Penelitian ini merupakan penelitian experimental dengan rancangan post test-only with control group dengan objek penelitian tikus putih Wistar. Penelitian ini terdapat dua kelompok sampel dengan masing-masing kelompok 16 ekor tikus. Kemudian dilakukan pemeriksaan MDA dan histopatologi glandula lakrimal . Penelitian dilakukan di Laboratorium Fakultas Farmasi Universitas Andalas, Laboratorium Patologi Anatomi RS Sitirahmah Padang dan Laboratorium Biokimia dan Biomedik Fakultas Kedokteran Universitas Andalas pada bulan Juli – September 2020.Hasil: Dari hasil penelitian tampak bahwa semua tikus yang mendapatkan paparan asap rokok terdapat kelainan histopatologi berupa infiltrasi sel radang yang disertai dengan kerusakan jaringan dan peningkatan kadar MDA glandula lakrimalnya. Pada glandula lakrimal tikus yang tidak terpapar asap rokok terdapat gambaran histopatologi yang normal, namun sebagian abnormal tetapi tanpa kerusakan struktur jaringan.Kesimpulan: Glandula lakrimal tikus yang terpapar asap rokok mempunyai gambaran histopatologi abnormal yang disertai dengan kerusakan struktur jaringan dan peningkatan kadar MDAKata Kuci : Glandula lakrimal, Asap rokok, MDA, Histopatologi